Pushing the boundaries of resistance: insights from Brachypodium-rust interactions - Figueroa, Melania; Castell-Miller, Claudia V.; Li, Feng; Hulbert, Scot H.; Bradeen, James M. (Frontiers in Plant Science, 2015)
The implications of global population growth urge transformation of current food and bioenergy production systems to sustainability. Members of the family Poaceae are of particular importance both in food security and for their applications as biofuel substrates. For centuries, rust fungi have threatened the production of valuable crops such as wheat, barley, oat, and other small grains; similarly, biofuel crops can also be susceptible to these pathogens. Emerging rust pathogenic races with increased virulence and recurrent rust epidemics around the world point out the vulnerability of monocultures. Basic research in plant immunity, especially in model plants, can make contributions to understanding plant resistance mechanisms and improve disease management strategies. The development of the grass Brachypodium distachyon as a genetically tractable model for monocots, especially temperate cereals and grasses, offers the possibility to overcome the experimental challenges presented by the genetic and genomic complexities of economically valuable crop plants. The numerous resources and tools available in Brachypodium have opened new doors to investigate the underlying molecular and genetic bases of plant–microbe interactions in grasses and evidence demonstrating the applicability and advantages of working with B. distachyon is increasing. Importantly, several interactions between B. distachyon and devastating plant pathogens, such rust fungi, have been examined in the context of non-host resistance. Here, we discuss the use of B. distachyon in these various pathosystems. Exploiting B. distachyon to understand the mechanisms underpinning disease resistance to non-adapted rust fungi may provide effective and durable approaches to fend off these pathogens. The close phylogenetic relationship among Brachypodium spp. and grasses with industrial and agronomic value support harnessing this model plant to improve cropping systems and encourage its use in translational research.